Recent radiotherapy could reduce heart-related death in patients with esophageal cancer: SEER database analysis - Yuta Sato; Rei Umezawa; Takaya Yamamoto; Noriyoshi Takahashi; Yu Suzuki; Keita Kishida; So Omata; Hinako Harada; Yasuhiro Seki; Nanae Chiba; Shinsaku Okuda; Keiichi Jingu (Cardio-Oncology)
Abstract Background There have been several reports showing that heart-related deaths are common in long-term survivors of esophageal cancer after radiation therapy; however, radiotherapy technology is evolving year by year. This study was carried out using the SEER database to determine whether the frequency of mortality from heart disease after radiotherapy has improved over time in patients with esophageal cancer. Methods SEER*Stat statistical software version 8.3.9.2 (National Cancer Institute) was used to perform case listing and data extraction. We reviewed causes of death in 8,297 patients who were treated by radiotherapy without surgery between 2004 and 2015 (radiotherapy group). For comparison with this group, we also reviewed causes of death in 5,149 patients who were treated by surgery without radiotherapy (surgery group). Results In the radiotherapy group, the cumulative heart-related death rate in patients with carcinoma in the middle to abdominal esophagus, for which it was considered that the heart was irradiated with a higher dose, was significantly higher than that in patients with carcinoma in the cervical to upper thoracic esophagus (p = 0.017). However, in the surgery group, the cumulative heart-related death rate in patients with carcinoma in the middle to abdominal esophagus tended to be lower than that in patients with carcinoma in the cervical to upper thoracic esophagus (p = 0.063). The cumulative heart-related death rate in patients treated in 2010–2015 was significantly lower than that in patients treated in 2004–2009 in the radiotherapy group (p = 0.011), although the cumulative heart-related death rate was not significantly different between patients treated in 2010–2015 and patients treated in 2004–2009 in the surgery group (p = 0.90). Conclusions The results suggest that recent advances in radiotherapy have enabled a reduction in radiation-induced heart disease in patients with esophageal cancer.